REFRESENTASI WANITA DIBALIK BERITA MEDIA INDONESIA - Erni Fitriani; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study discusses sexual violence against women in online media coverage. Good media can present balanced and accurate information. Various news reports related to sexual harassment, which are often experienced by women, represent individuals within a discourse. Today, the exploitation of women is carried out in more intellectual ways and is cleverly packaged, one of which is through the discourse conveyed in mass media. Women in the media are positioned prominently in visual terms but are marginalized in meaning. If this continues, it will reinforce the gender disparity between women and men, leading to the potential rise of gender oppression with women as the victims. The issue addressed in this research is discourse analysis using Sara Mills' theory. Sara Mills’ discourse theory revolves around feminist discourse analysis, where she examines how women are portrayed in the news. The research method used in this study is a literature review. The results of this study conclude that the text exhibits bias in representing women in news texts across three different media platforms. Keywords: Discourse Analysis, Sexual Harassment, Sara Mills